The Effectiveness of the OIDDE Learning Model in Improving Tenth-Grade Students’ Critical Thinking Skills and Scientific Literacy on Ecosystem and Environmental Change Topics - Ibrahim, Pua; Miftachul Hudha, Atok; Husamah, H.; Mirza Nuryady, Moh. (Biosfer: Jurnal Tadris Biologi, 2026)
This study investigated whether the OIDDE learning model could improve tenth-grade students’ critical thinking skills and scientific literacy in biology, particularly in ecosystem and environmental change topics. A quasi-experimental pretest–posttest non-equivalent control group design was used with 58 students from MAN Ende, East Nusa Tenggara. The experimental class was taught through the OIDDE stages, whereas the control class received conventional instruction. Data were collected using essay-based critical thinking tests and multiple-choice scientific literacy tests. The results showed that students in the experimental class achieved higher post-test scores in critical thinking skills (M = 83.40) than those in the control class (M = 59.29). The experimental class also obtained a high N-gain score of 72.29% and a very large effect size (d = 2.75). A similar result was found for scientific literacy, with the experimental class achieving a higher mean score (M = 85.33) than the control class (M = 55.71), a high N-gain score of 76.10%, and a very large effect size (d = 2.87). The statistical results confirmed significant differences between the two groups (p < .001). These findings suggest that OIDDE provides a structured learning pathway that helps students examine biological problems, discuss evidence, make decisions, and connect learning with responsible behavior. Efektivitas Model Pembelajaran OIDDE dalam Meningkatkan Keterampilan Berpikir Kritis dan Literasi Sains Siswa Kelas X pada Materi Ekosistem dan Perubahan Lingkungan ABSTRAK: Penelitian ini mengkaji apakah model pembelajaran OIDDE dapat meningkatkan keterampilan berpikir kritis dan literasi sains siswa kelas X dalam pembelajaran biologi, khususnya pada materi ekosistem dan perubahan lingkungan. Penelitian ini menggunakan desain kuasi eksperimen dengan pola pretest–posttest non-equivalent control group yang melibatkan 58 siswa dari MAN Ende, Nusa Tenggara Timur. Kelas eksperimen diajar melalui tahapan OIDDE, sedangkan kelas kontrol memperoleh pembelajaran konvensional. Data dikumpulkan menggunakan tes berpikir kritis berbasis esai dan tes literasi sains berbentuk pilihan ganda. Hasil penelitian menunjukkan bahwa siswa pada kelas eksperimen memperoleh skor post-test keterampilan berpikir kritis yang lebih tinggi (M = 83,40) dibandingkan siswa pada kelas kontrol (M = 59,29). Kelas eksperimen juga memperoleh skor N-gain tinggi sebesar 72,29% dan effect size yang sangat besar (d = 2,75). Hasil serupa juga ditemukan pada literasi sains, dengan kelas eksperimen memperoleh skor rata-rata yang lebih tinggi (M = 85,33) dibandingkan kelas kontrol (M = 55,71), skor N-gain tinggi sebesar 76,10%, dan effect size yang sangat besar (d = 2,87). Hasil statistik mengonfirmasi adanya perbedaan yang signifikan antara kedua kelompok (p < 0,001). Temuan ini menunjukkan bahwa OIDDE menyediakan alur pembelajaran terstruktur yang membantu siswa mengkaji permasalahan biologi, mendiskusikan bukti, mengambil keputusan, dan menghubungkan pembelajaran dengan perilaku yang bertanggung jawab.